Efficiency Improvement of TiO2 Nanorods Electron Transport Layer Based Perovskite Solar Cells by Solvothermal Etching - Jarwal D.K.; Kumar A.; Mishra A.K.; Ratan S.; Kumar C.; Upadhyay D.; Mukherjee B.; Jit S. (My University, 2025)
The efficiency improvement of perovskite solar cells (PSCs) by solvothermal etching and/or TiCl4 treatment of TiO2 nanorod arrays (NRAs) based electron transport layer (ETL) is reported in this article. The TiO2 NRAs are explore for the ETL because of their better direct carrier transportation over other TiO2 nanostructures. The solvothermal etching of TiO2 NRAs enhances the surface-to-volume ratio of the ETL, which, in turn, enhances the power conversion efficiency (PCE) of the PSCs. All the measurements are performed at room temperature and high humid (with ∼65% humidity) conditions to demonstrate the performance of the PSCs under normal environmental conditions. A noteworthy efficiency of 15.16% with an improved fill factor and short circuit current density (JSC) is achieved in the proposed PSCs under this article. The performance of the PSC is shown to improve further by exploring TiCl4 treatment of the solvothermally etched TiO2 NRs as the ETL in the device. © 2011-2012 IEEE.